Efficient production of flavonoids in Fagopyrum tataricum hairy root cultures with yeast polysaccharide elicitation and medium renewal process - Zhao, Jiang-Lin (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: Tartary buckwheat (Fagopyrum tataricum), an excellent edible and medicinal crop, has been widely used as a daily diet and traditional medicine for a long time. The major functional components of Fagopyrum tataricum have been demonstrated to be flavonoids (i.e. rutin and quercetin), which had notable andioxidant, antidiabetic, hypocholesterolemic and antitumor activities. Hairy root culture is a convenient and efficient plant tissue culture system for large scale production of bioactive metabolites. OBJECTIVE: To enhance the functional flavonoids production in hairy root culture of F. tataricum. MATERIALS AND METHODS: The elicitation treatment in combination with medium renewal strategy was applied for efficient promoting flavonoids production in F. tataricum hairy root cultures. RESULTS: The exogenous yeast polysaccharide (YPS) elicitor notably stimulated the functional metabolites production in F. tataricum hairy root cultures, and the stimulation effect was concentration-dependent. Combination with the YPS elicitation (200 mg/L) and medium renewal process, the maximal flavonoids yield was enhanced to 47.13 mg/L, about 3.2-fold in comparison with the control culture of 14.88 mg/L. Moreover, this research also revealed the accumulation of these bioactive metabolites resulted from the stimulation of the phenylpropanoid pathway by YPS treatment. These results indicated that the F. tataricum hairy root culture could be an effective system for rutin and quercetin production.